2007
DOI: 10.1086/520716
|View full text |Cite
|
Sign up to set email alerts
|

SpitzerQuasar and ULIRG Evolution Study (QUEST). II. The Spectral Energy Distributions of Palomar‐Green Quasars

Abstract: This is the second paper studying the QSOs in the Spitzer QUEST sample. Previously we presented new PAH measurements and argued that most of the observed far-infrared ( FIR) radiation is due to star-forming activity. Here we present spectral energy distributions (SEDs) by supplementing our data with optical, NIR, and FIR observations. We define two subgroups, of ''weak FIR'' and ''strong FIR'' QSOs, and a third group of FIR nondetections. Assuming a starburst origin for the FIR, we obtain ''intrinsic'' active … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

57
487
7
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 334 publications
(552 citation statements)
references
References 42 publications
57
487
7
1
Order By: Relevance
“…Netzer et al (2007) found for luminous PG QSOs that this relationship has a slope of α ≈ 0.8 (see black dotted line in Fig. 9).…”
Section: The Star Formation Dependence On Agn Activitymentioning
confidence: 81%
See 2 more Smart Citations
“…Netzer et al (2007) found for luminous PG QSOs that this relationship has a slope of α ≈ 0.8 (see black dotted line in Fig. 9).…”
Section: The Star Formation Dependence On Agn Activitymentioning
confidence: 81%
“…Therefore, we interpret the FIR emission as being powered by star formation (e.g. Rowan-Robinson 1995; Schweitzer et al 2006;Netzer et al 2007), and we represent it with a black-body modified by frequencydependent emissivity component (Hildebrand 1983), given by…”
Section: Sed Fittingmentioning
confidence: 99%
See 1 more Smart Citation
“…Lutz et al 2008;Hernán-Caballero et al 2009) as well as low redshift ones (e.g. Netzer et al 2007). However, at shorter wavelengths the continuum slope is increasingly steep and interrupted only by a prominent Paschen α line.…”
Section: Composite Spectramentioning
confidence: 99%
“…A popular method to distinguish star formation and AGN activity is to rely on Spectral Energy Distribution (SED) models. Some studies involving SED analysis are Elvis et al (1994), Richards et al (2006), Netzer et al (2007), Mor & Netzer (2012), Leipski et al (2013Leipski et al ( , 2014, and Xu et al (2015aXu et al ( , 2015b. In this work, we use a Python-based custom-written SED fitting routine (available upon inquiry).…”
Section: Introductionmentioning
confidence: 99%